PERBANDINGAN METODE SPEKTROFOTOMETRI UV-VIS DAN IODIMETRI DALAM PENENTUAN ASAM ASKORBAT SEBAGAI BAHAN AJAR KIMIA ANALITIK MAHASISWA JURUSAN TEKNOLOGI PERTANIAN BERBASIS OPEN-ENDED EXPERIMENT DAN PROBLEM SOLVING - Iskandar, Dodi (IST AKPRIND YOGYAKARTA, 2017)
This study aims to know the difference through statistical analysis from two methods in determining content of ascorbic acid in tablet (brand CIPI). This experiment is done in twenty repetition. Each of two methods did twelve times. The mass of tablet CIPI is 2,0 gram. Shapiro-Wilk Normality Test shows that the value of spectrophotometry uv-vis is 0.9714 and the value of eudiometry is 0.08261. Both of them is bigger than 0,05. Based on statistical analysis, the both of methods have normal distribution. Then, Paired T-Test is applied. The result shows that hypothesis (Ho) is accepted. This means that two method have no real difference.